Changes in Bullying Experiences and Mental Health Problems Among Adolescents Before and After the COVID-19 Pandemic in Greece - Giannakopoulos, Georgios; Zaravinos-Tsakos, Foivos; Mastrogiannakou, Maria; Sourander, Andre; Kolaitis, Gerasimos (MDPI AG, 2025)
Bullying poses significant challenges to adolescent health and well-being. This time-trend study examined the impact of the COVID-19 pandemic on bullying behaviors and associated emotional and behavioral difficulties among Greek adolescents. Data were collected from two cross-sectional surveys in 2016 (n = 1574) and 2023 (n = 5753) conducted in Greece. Both samples comprised students aged 12-16 years, with near-equal gender distribution (2016, 53.4% girls; 2023, 54.5% girls) and a predominance of urban residents (approximately 73% in both samples). Traditional and cyberbullying experiences were assessed via structured questionnaires, while mental health outcomes were measured using the Strengths and Difficulties Questionnaire (SDQ). Post-pandemic findings revealed substantial increases in bullying involvement; traditional bullying victimization rose from 12.4% to 21.7%, and cyberbullying victimization increased from 4.0% to 11.6%. Correspondingly, mean SDQ total scores increased significantly from 8.59 to 14.16, reflecting heightened emotional and behavioral problems. Logistic regression analyses identified male gender, urban residence, and non-traditional family structures as significant predictors of bullying involvement. These results underscore the amplified burden of bullying and mental health difficulties in the post-pandemic era, highlighting the urgent need for targeted prevention and intervention strategies to address both traditional and cyberbullying within diverse sociodemographic contexts.